Akibat Wanprestasi yang Dilakukan Penyewa dalam Perjanjian Sewa Menyewa Lahan Bangunan - Mohammad Sahrir Syarif; Yusuf M. Said; Gunawan Nachrawi (Syntax Corporation, 2023)
The relationship between renting and individual is very close because it often occurs in everyday life because people are unable to live without help from other parties such as renting goods that are to other parties. Rent that often occurs in the community is renting a house or building, both for individuals and groups. In renting a house, most parties often make mistakes both on the landlord and the tenant of the house, causing disputes between both parties. The research method used is the normative juridical method, namely research that prioritizes literature data, namely research on secondary data. The secondary data can be primary, secondary or tertiary legal material. This research includes research on the Effects of Default by Tenants in Lease Agreements and Judges' Considerations in Decision Number 217/PDT/2020/PT SBY. Based on the results of the study, the author concludes that with the act of default in the rental agreement, the aggrieved party has the right to take actions to fulfill the performance that has been agreed, an agreement has an impact if the agreement is not fulfilled by one party, then the other party has the right to make legal remedies or claims. A judge's judgment on default is a judgment to enforce the law, that is, a judgment that is sometimes rendered when compensation will not be a viable legal remedy. This judgment is a court order that orders the offending party to carry out his promises with the threat of punishment for violating the court decision and an Order not to violate the agreement, namely: A judgment is a court order directed to a person not to violate his agreement.